P174 Upadacitinib response rates in patients with psoriatic arthritis enrolled in the SELECT-PsA-1 and SELECT-PsA-2 trials assessed according to modified PsARC. (26th April 2021) - Coates, Laura C; Garrood, Toby; Gullick, Nicola; Helliwell, Philip; Kent, Toby; Marks, Jonathan; Tillett, William; Kaur-Papadakis, Daljit; Tahir, Hasan; Haaren, Stijn van; McInnes, Iain
Abstract: Background/Aims   The objective of this analysis was to describe the upadacitinib (UPA) response rates of patients with psoriatic arthritis (PsA) enrolled in the SELECT-PsA-1 and SELECT-PsA-2 randomised controlled trials according to modified Psoriatic Arthritis Response Criteria (PsARC). The UK National Institute for Health and Care Excellence recommends assessing PsA treatment responses using PsARC (advanced therapy-specific time points: after weeks [W] 12, 16 or 24). Methods   PsARC responses were assessed from W2 through W24 post-initiation for patients enrolled in SELECT-PsA-1 (upadacitinib 15 mg once-daily [UPA-15mg], placebo and adalimumab 40 mg every other week [ADA] treatment arms) and SELECT-PsA-2 (UPA-15mg and placebo treatment arms). PsARC responses were derived from tender joint count 68 (TJC), swollen joint count 66 (SJC), patient global self-assessment (PtGA) and physician global assessment (PGA) and analysed using non-responder imputation. Results   UPA-15mg PsARC response rates increased progressively from W2 through to W12 in SELECT-PsA-1 (78.3%) and SELECT-PsA-2 (70.6%; see Table ). Despite relatively high placebo response rates, UPA-15mg response rates were statistically significantly higher than placebo at all assessments between W2 and W24 in SELECT-PsA-1 and SELECT-PsA-2 and were statistically significantly higher than ADA from W20 (SELECT-PsA-1; see Table ). Baseline characteristics (including sex, PsA duration, body mass index, tobacco use, body surface area ≥3%, enthesitis and dactylitis) were generally balanced between W24 PsARC responders and non-responders in each SELECT-PsA-1 and SELECT-PsA-2 treatment arm. Differences in PsARC response rates at W24 for UPA-15mg versus placebo (pooled SELECT-PsA-1 and SELECT-PsA-2 data) and versus ADA (SELECT-PsA-1) were similar in patients stratified by baseline characteristics and in patients receiving UPA-15mg monotherapy versus combination therapy. By W12, UPA-15mg response rates for individual PsARC components (SJC and TJC: ≥30% improvement; PtGA and PGA: ≥20% improvement) ranged between 77.6%-89.5% in SELECT-PsA-1 and between 70.1%-82.5% in SELECT-PsA-2. Conclusion   PsARC responses greater than placebo were seen as early as W2, with stable response rates from W12 in both SELECT-PsA-1 and SELECT-PsA-2. Statistically significantly higher response rates versus ADA were observed by W20. Differences in W24 PsARC responses versus placebo and versus ADA were generally consistent across baseline characteristics and UPA-15mg mono/combination therapy. Disclosure   L.C. Coates: Consultancies; AbbVie, Amgen, Boehringer-Ingelheim, BMS, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Sun Pharma, and UCB. Honoraria; AbbVie, Amgen, Boehringer-Ingelheim, BMS, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Sun Pharma, and UCB. Member of speakers' bureau; AbbVie, Amgen, Boehringer-Ingelheim, BMS, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Sun Pharma, and UCB. Grants/research support; AbbVie, Amgen, Boehringer-Ingelheim, BMS, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Sun Pharma, and UCB. T. Garrood: Consultancies; AbbVie, Pfizer and Gilead. Honoraria; AbbVie, Pfizer and Gilead. Grants/research support; AbbVie, Pfizer and Gilead. N. Gullick: Consultancies; AbbVie, Celgene, Eli Lilly, Izana, Janssen, Novartis and UCB. Member of speakers' bureau; AbbVie, Celgene, Eli Lilly, Izana, Janssen, Novartis and UCB. Grants/research support; AbbVie, Celgene, Eli Lilly, Izana, Janssen, Novartis and UCB. P. Helliwell: Consultancies; Eli Lilly. Other; fees for educational services from Pfizer, Novartis and Janssen. T. Kent: Corporate appointments; Employee of AbbVie. Shareholder/stock ownership; may own AbbVie stocks. J. Marks: Honoraria; AbbVie, Gilead, Novartis, Pfizer and UCB for participation in advisory boards and to support educational activities unrelated to the publication. W. Tillett: Consultancies; Lilly, Pfizer, AbbVie, Celgene, UCB, and Novartis. Honoraria; Lilly, Pfizer, AbbVie, Celgene, UCB, and Novartis. Member of speakers' bureau; AbbVie, Janssen and Celgene. Grants/research support; Lilly, Pfizer, AbbVie, Celgene, UCB, and Novartis. D. Kaur-Papadakis: Corporate appointments; Employee of AbbVie. Shareholder/stock ownership; may own AbbVie stocks. H. Tahir: Consultancies; Fees for consultation or participation in advisory boards from AbbVie, Novartis, Pfizer, UCB, Eli-Lilly and Janssen. Other; Education Grants from Novartis and Pfizer. S. van Haaren: Corporate appointments; Employee of AbbVie. Shareholder/stock ownership; may own AbbVie stocks. I. McInnes: Honoraria; Bristol-Myers Squibb, Celgene, Eli Lilly and Company, AbbVie, Gilead, Janssen, Novartis, Pfizer, and UCB. Grants/research support; Bristol-Myers Squibb, Celgene, Eli Lilly and Company, AbbVie, Gilead, Janssen, Novartis, Pfizer, and UCB.